Inorganic prebaked anode steel claw coating as well as preparation method and application thereof

By using a multi-phase inlaid coating system with composite adhesive and composite sustained release passivator on the anode steel claw, the existing coatings are solved in high temperature and strong corrosion environments, achieving a more efficient protection effect, extending service life and reducing production costs.

CN119875398AActive Publication Date: 2025-04-25HUNAN ZHIQI TECHNOLOGY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411843206.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-25
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

The existing pre-baked anode steel claw coating is prone to fall off under high temperature and strong corrosion environments, and has poor tolerance, resulting in corrosion and oxidation of steel claws, affecting aluminum electrolytic production efficiency and cost.

Method used

A multi-phase inlay, step-distribution and composite phase toughening coating system with composite adhesives and composite sustained release passivating agents is used to provide both physical and chemical protection to form a three-dimensional interwoven protection system.

Benefits of technology

It significantly improves the corrosion resistance and service life of the anode steel claws, maintains the conductivity uniformity of the electrolytic cell, reduces the cost of overhaul of the steel claws, and improves the efficiency of aluminum electrolytic production and primary aluminum quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a prebaked anode steel claw coating formula and a preparation method and application thereof.The prebaked anode steel claw coating can be used for forming a protective coating on the surface layer of a steel claw and comprises 5-50 parts of a composite binder, 0.1-5 parts of a composite slow-release passivator and a solvent; the composite slow-release passivator comprises phosphate and a corrosion inhibitor; the composite binder comprises sol, water glass and a boron-containing compound. The preparation method comprises the following steps: (1) crushing raw materials; and (2) grinding and mixing the raw materials and the solvent in proportion. According to the prebaked anode steel claw coating disclosed by the invention, a comprehensive protection mode of combining chemical passivation and structural strengthening is adopted for a base material, so that the coating has the advantages of high strength, high hardness, strong impact resistance, good tolerance and strong permeability resistance, and continuous protection of the coating on the base material is ensured; the preparation method is simple, raw materials are easy to obtain, and the method is suitable for large-scale industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of electrolytic anode materials, and in particular to a prebaked anode steel claw coating and a preparation method and application thereof. Background Art

[0002] Prebaked anode steel claws are important components in the production of electrolytic aluminum. They connect the anode carbon block and the aluminum guide rod, bear the weight of the anode, and transmit ultra-large capacity current. At high temperatures of 400-900°C, the anode steel claws are susceptible to baking, erosion, and impact by electrolytes, top covering materials, air, and electrolytic flue gas. At the same time, they are also subject to damage from periodic heat treatment, thermal deformation stress, electromagnetic force, and collision force, which can easily lead to corrosion, wear, and shedding of the steel claw surface, causing serious damage to the steel claws, destruction of cross-sectional uniformity, and affecting the uniformity of electrolytic cell conductivity, thereby reducing the production efficiency of aluminum electrolysis and significantly increasing the operating cost of electrolytic aluminum. The consumption of anode steel claws is an important economic and technical indicator of aluminum electrolysis production. According to statistics, taking an enterprise with an annual output of 200,000 tons of primary aluminum as an example, when the steel claws are severely corroded, the average service life of the anode steel claws is about 16 cycles, and the annual replacement and repair costs are as high as more than 8 million yuan. The cost increase caused by the imbalance of conductive uniformity is significantly higher than this data. In addition, the corrosion products formed after the steel claws are corroded will enter the electrolyte, affecting the quality of the primary aluminum, the distribution of current, and the correct judgment of the operating conditions of the electrolytic cell.

[0003] In the aluminum electrolysis production process, in order to prevent the anode steel claws from being washed and corroded by the electrolyte, protective measures need to be taken for the anode steel claws. However, the anti-corrosion, anti-oxidation and anti-delamination of the anode steel claws have always been thorny issues faced by the aluminum electrolysis industry. How to reduce the corrosion, oxidation and erosion of the anode steel claws is of great significance to extending the service life of the steel claws, improving the quality of the original aluminum and reducing the production cost. In the existing technology, the use of coating methods to protect the steel claws is a relatively common technical means.

[0004] Currently, there are two main technical directions for the common surface treatment technologies of pre-baked anode steel claws. One is to use substrate passivation technology, which adopts the passivation or alloying technology mechanism to form an anti-corrosion layer on the surface of the steel claw; the other is to use the technical idea of ​​adding a maintenance structure to the outer layer of the anode steel claw, such as a high-temperature resistant coating, to directly protect the anode steel claw and prevent various forms of erosion.

[0005] For example, patent documents 202311639160.6, 202310080536.8, 202210835478.0, and 201710842416.1 all adopt the above method. Although these existing paints and coatings have protected the anode steel claws to a certain extent, they still have problems such as long process flow, weak impact resistance of the anti-corrosion protective layer, easy failure of the passivation protection effect under cyclic temperature difference use environment, easy falling off under continuous high temperature and strong corrosion conditions, and poor tolerance. Summary of the invention

[0006] The present invention provides a prebaked anode steel claw coating and a preparation method and application thereof, so as to solve the technical problems that the existing steel claw coatings have poor corrosion resistance, tolerance and anti-surface failure effect under extreme use environments due to single or unbalanced performance.

[0007] In order to solve the above technical problems and achieve the technical effects, the present invention adopts the following technical solutions: A prebaked anode steel claw coating comprises the following components in parts by weight: 5~50 parts of composite binder, 0.1~5 parts of composite slow-release passivator and solvent; The composite slow-release passivating agent comprises phosphate and corrosion inhibitor, wherein the phosphate comprises one or two of zirconium-based phosphate, aluminum-based phosphate, magnesium-based phosphate, calcium-based phosphate, chromium-based phosphate and sodium-based phosphate; the corrosion inhibitor comprises a combination of at least two of chromate, nitrate, nitrite, borate, tungstate, benzoic acid, zinc sulfate and acidic calcium carbonate; The composite binder comprises sol, water glass and a boron-containing compound.

[0008] The design idea of ​​the above technical solution is that the present invention provides dual protection at the physical and chemical levels respectively through the composite binder and the composite slow-release passivator. On the one hand, the composite slow-release passivator is selected to provide chemical protection for the anode at the oxidation and adsorption levels. On the other hand, the surface precipitation film formed by the composite binder is used to provide physical protection for the anode. At the same time, the composite slow-release passivator and the composite binder form a three-dimensional interwoven, multi-phase inlaid, and stepped distribution protection system. While ensuring the continuous and stable performance of their respective performance, the structural strength, density, spreading effect, mechanical properties and slow-release effect of the coating are promoted, bringing continuous and effective physical and chemical protection to the anode steel claw, achieving the purpose of continuously preventing the steel claw from being eroded, maintaining the steel claw in good working condition, and extending the service life of the steel claw, and ultimately maintaining the uniform electrical balance of the anode, improving the performance indicators of the electrolytic cell, and significantly reducing the overhaul cost of the steel claw.

[0009] In the design of the composite slow-release passivating agent, the composite passivation system formed by phosphate and corrosion inhibitor utilizes the characteristic that phosphate will gradually decompose under high temperature environment. By adjusting the release rate of the passivation factor produced by the corrosion inhibitor, it plays a continuous passivation effect on the surface of the steel claw. In the design of the composite binder, the water glass in the composite binder will not melt directly under the temperature conditions of the electrolytic cell, but will first be transformed into a colloidal state. The melt formed by compounding with the boron-containing compound at different temperatures can fill the gaps generated by the decomposition of the substrate and the coating, thereby improving the sealing and stability of the coating material; and then combining with other structural materials in the coating under high temperature environment to improve its overall impact resistance and shear resistance, so that the solidification bond between the coating and the substrate is more dense and stable, showing good mechanical strength and excellent acid resistance. The basic adhesion and film-forming stability of the sol material are good, and the compatibility between the boron-containing compound and water glass and other material components in the formula and the high-temperature reaction joint strengthening are good. Together with the boron-containing compound and water glass, the technical problems of poor coating tolerance and easy shedding under continuous high temperature and strong corrosion conditions are reduced.

[0010] As a further preferred embodiment of the above technical solution, the mass ratio of the phosphate to the corrosion inhibitor is 1:(1-2.5).

[0011] As a further preferred embodiment of the above technical solution, the sol includes at least one of aluminum sol or aluminum silicate sol; the water glass includes at least one of lithium water glass and potassium water glass; and the boron-containing compound is one or two of boron oxide, boron nitride, titanium boride, borax, chromium boride, calcium boride and boric acid.

[0012] As a further preferred embodiment of the above technical solution, the prebaked anode steel claw coating also includes 5 to 30 parts by weight of a structural reinforcing agent, which includes a skeleton material and kaolin; the skeleton material includes at least one of barite, glass powder, silicon powder and mica powder; the mass proportion of kaolin in the structural reinforcing agent is 5% to 50%. Filling powders such as barite and glass powder have stable chemical properties, especially in the working environment of hydrofluoric acid in the electrolytic cell, so they can increase the thickness, strength and durability of the coating, and can be partially converted into a co-solvent in the high temperature area and block the gaps caused by the reaction or volatilization of other materials in the coating under high temperature acidic conditions; at the same time, the filling powder with a considerable specific surface area has a good wrapping effect on other materials under the combined effect of the plasticity, bonding and viscosity of kaolin (thickening, dispersion, structural strengthening), reducing the loss of the coating under high temperature, high cavitation and high impact environment, and ensuring the mechanical properties of the coating and the bonding effect with the substrate. The structural reinforcing agent can participate in the construction of the protective system of the composite slow-release passivating agent and the composite binder mentioned above, and together they can be inlaid, reconstructed and cured to form a protective coating with multi-phase inlay, step distribution and composite phase toughening.

[0013] As a further preferred embodiment of the above technical solution, the total ignition reduction rate of the prebaked anode steel claw coating is ≤10%, and the total organic component mass is ≤5%. The volatilization of the solvent during the film formation process of the coating at a continuous high temperature will cause defects such as micropores and pinholes in the coating, which makes the corrosion resistance of the coating have obvious defects; the organic coating is exposed to the corrosive environment for a long time, and the leaching of the coating components due to acid cavitation will also cause pore formation, thereby accelerating coating damage and corrosion of the metal substrate; in addition, considering the high temperature environment of the electrolytic cell, the organic components will produce volatiles and VOCs during use, which will bring safety and environmental impacts. Therefore, the present invention uses inorganic materials to form the coating system to reduce the occurrence of the above situation.

[0014] Based on the same technical concept, the present invention also provides a method for preparing the above-mentioned prebaked anode steel claw coating, comprising the following steps: (1) crushing the passivator, boron-containing compound, and structural reinforcing agent of the prebaked anode steel claw coating alone or in combination; (2) The dissociated raw material is mixed with other raw materials in proportion and a portion of solvent is added for wet grinding. After grinding, the remaining solvent is added and mixed to obtain the prebaked anode steel claw coating.

[0015] As a further preferred embodiment of the above technical solution, in step (1), the particle size of the raw material after dissociation is controlled to be less than 150 um.

[0016] As a further preferred embodiment of the above technical solution, in step (2), the particle size of the raw material after grinding is controlled to be less than 45 um.

[0017] As a further preferred embodiment of the above technical solution, in step (2), the stirring speed of the mixing operation is 200-500 rpm, and the mixing time is 15-60 min.

[0018] Based on the same technical concept, the present invention also provides an application of the above-mentioned prebaked anode steel claw coating, which is used to form a protective coating on the surface of the prebaked anode steel claw used in the electrolytic aluminum process.

[0019] As a further preferred embodiment of the above technical solution, the application of the above prebaked anode steel claw coating specifically includes the following steps: (1) The prebaked anode steel claw coating is uniformly applied on the surface of the prebaked anode steel claw by spraying or brushing; (2) Drying and curing the steel claw coated with the paint to obtain an anode steel claw coated with a protective coating.

[0020] As a further preferred embodiment of the above technical solution, after the prebaked anode steel claw coating is evenly coated on the surface of the prebaked anode steel claw, the surface of the anode steel claw is pre-treated by sandblasting to make its surface meet the rust removal grade Sa2.5.

[0021] As a further preferred embodiment of the above technical solution, the coating thickness in step (1) is greater than or equal to 100 μm.

[0022] As a further preferred embodiment of the above technical solution, the drying and curing treatment in step (2) is natural air drying and curing or oven drying and curing, and the time for natural air drying is more than 24 hours; the temperature for oven drying and curing is 35-60°C, and the drying time is more than 4 hours.

[0023] Compared with the prior art, the advantages of the present invention are: (1) The prebaked anode steel claw coating of the present invention adopts a coating system formulation design path of multi-phase inlay, stepped distribution, composite phase toughening and slow-release composite passivation, and adopts a coating protection system combining chemical passivation and physical protection for the substrate, thereby reducing the decline in the comprehensive performance of the coating such as continuous anti-oxidation, impact resistance and corrosion resistance under high temperature environment, and can meet the steel claw protection needs of the electrolytic cell under high dust, high temperature, high thermal vibration, high cavitation and high impact environment.

[0024] (2) The preparation method of the prebaked anode steel claw coating of the present invention is simple, the raw materials are easily available, and it is suitable for large-scale industrial production. DETAILED DESCRIPTION

[0025] The present invention is further described in detail below in conjunction with specific embodiments.

[0026] Embodiment 1: The prebaked anode steel claw coating of this embodiment includes a composite binder, a composite slow-release passivating agent, an auxiliary agent and a solvent (water).

[0027] The composite slow-release passivating agent includes the following components in parts by mass: 2 parts of sodium-based phosphate and aluminum-based phosphate (mass ratio is 1:1), 1.5 parts of chromate and nitrite (sodium chromate and sodium nitrite in a mass ratio of 1:1 are selected in this embodiment).

[0028] The composite binder includes the following components in parts by mass: 20 parts of aluminum sol, 15 parts of lithium water glass and 8 parts of calcium boride.

[0029] The auxiliary agent includes the following components in parts by weight: 0.3 parts of calcium borate, 0.2 parts of suspending agent, 0.5 parts of dispersant and 1 part of thickener.

[0030] The preparation method of the prebaked anode steel claw coating of this embodiment comprises the following steps: (1) Grind each component to ensure that the particle size is ≤45μm.

[0031] (2) Test and screen the components after grinding to ensure that the quality meets the requirements.

[0032] (3) The raw materials of the composite binder and the composite slow-release passivator are respectively fed into different mixers for thorough mixing.

[0033] (4) Add the mixed composite slow-release passivator raw material to the composite binder raw material and stir to mix, and add the solvent and stir at a speed of 300 rpm for 30 minutes to obtain the prebaked anode steel claw coating of this embodiment.

[0034] The prebaked anode steel claw coating of this embodiment is used to form a protective coating on the surface of the prebaked anode steel claw used in the aluminum electrolysis process. The specific method includes the following steps: (1) Pre-treatment of the surface of the anode steel claw by sandblasting to make it meet the rust removal grade Sa2.5. Sa2.5 rust removal grade standard: Thoroughly spray abrasives to completely remove rust and scale. After removing dust, the steel surface has a nearly white metallic luster with only tiny marks.

[0035] (2) The pre-baked anode steel claw coating is applied to the surface of the pre-baked anode steel claw by spraying according to the standard method (the coating thickness is 120 μm).

[0036] (3) The steel claws coated with the paint are subjected to natural air drying and curing treatment. The natural air drying and curing time is 48 hours, and the anode steel claws coated with the protective coating are obtained.

[0037] The above-mentioned anode steel claws coated with protective coating were tested, and the test methods and results are as follows: The test method refers to the standard: GB / T 21776-2008 "Guide to the Testing Standards of Powder Coatings and Their Coatings". The adhesion, compressive strength and corrosion resistance of the coating were tested. The results are shown in Table 1.

[0038] Embodiment 2: The prebaked anode steel claw coating of this embodiment includes a composite binder, a composite slow-release passivating agent, a structural reinforcing agent, an auxiliary agent and a solvent (water).

[0039] The composite slow-release passivating agent includes the following components in parts by mass: 2 parts of sodium-based phosphate and aluminum-based phosphate (mass ratio is 1:1), 1.5 parts of chromate and nitrite (sodium chromate and sodium nitrite in a mass ratio of 1:1 are selected in this embodiment).

[0040] The composite binder includes the following components in parts by mass: 20 parts of aluminum sol, 15 parts of lithium water glass and 8 parts of calcium boride.

[0041] The structural reinforcing agent includes the following components in parts by mass: 25.5 parts of a framework material and 4.5 parts of kaolin, wherein the framework material includes barite, silica powder, mica powder and glass powder (the mass ratio is 1:1:1:1).

[0042] The auxiliary agent includes the following components in parts by weight: 0.5 parts of calcium borate, 0.3 parts of suspending agent, 1 part of dispersant and 1.5 parts of thickener.

[0043] The preparation method of the prebaked anode steel claw coating of this embodiment comprises the following steps: (1) Grind each component to ensure that the particle size is ≤45μm.

[0044] (2) Test and screen the components after grinding to ensure that the quality meets the requirements.

[0045] (3) The raw materials of the composite binder and the composite slow-release passivator are respectively fed into different mixers for thorough mixing.

[0046] (4) Add the mixed composite slow-release passivator raw material to the composite binder raw material and stir to mix, and add the solvent and stir at a speed of 300 rpm for 30 minutes to obtain the prebaked anode steel claw coating of this embodiment.

[0047] The prebaked anode steel claw coating of this embodiment is used to form a protective coating on the surface of the prebaked anode steel claw used in the aluminum electrolysis process. The specific method includes the following steps: (1) Pre-treatment of the surface of the anode steel claw by sandblasting to make it meet the rust removal grade Sa2.5. Sa2.5 rust removal grade standard: Thoroughly spray abrasives to completely remove rust and scale. After removing dust, the steel surface has a nearly white metallic luster with only tiny marks.

[0048] (2) The pre-baked anode steel claw coating is applied to the surface of the pre-baked anode steel claw by spraying according to the standard method (the coating thickness is 120 μm).

[0049] (3) The steel claws coated with the paint are subjected to natural air drying and curing treatment. The natural air drying and curing time is 48 hours, and the anode steel claws coated with the protective coating are obtained.

[0050] The above-mentioned anode steel claws coated with protective coating were tested, and the test methods and results are as follows: The test method refers to the standard: GB / T 21776-2008 "Guide to the Testing Standards of Powder Coatings and Their Coatings". The adhesion, compressive strength and corrosion resistance of the coating were tested. The results are shown in Table 1.

[0051] In order to explore the effect of the change of kaolin content in the structural reinforcing agent on the coating performance, while keeping other components and operations unchanged, this example adjusted the mass proportion of kaolin in the structural reinforcing agent, and tested the corresponding coating properties obtained. The results are shown in Table 2.

[0052] Embodiment 3: The prebaked anode steel claw coating of this embodiment includes a composite binder, a composite slow-release passivating agent, a structural reinforcing agent, an auxiliary agent and a solvent (water).

[0053] The composite slow-release passivating agent includes the following components in parts by mass: 2 parts of sodium-based phosphate and aluminum-based phosphate (mass ratio is 1:1), 2.5 parts of chromate and nitrite (sodium chromate and sodium nitrite are selected in a mass ratio of 1:1 in this embodiment).

[0054] The composite binder includes the following components in parts by mass: 20 parts of aluminum sol, 15 parts of lithium water glass and 8 parts of calcium boride.

[0055] The structural reinforcing agent includes the following components in parts by mass: 25.5 parts of a framework material and 4.5 parts of kaolin, wherein the framework material includes barite, silica powder, mica powder and glass powder (the mass ratio is 1:1:1:1).

[0056] The auxiliary agent includes the following components in parts by weight: 0.5 parts of calcium borate, 0.3 parts of suspending agent, 1 part of dispersant and 1.5 parts of thickener.

[0057] The preparation method of the prebaked anode steel claw coating of this embodiment comprises the following steps: (1) Grind each component to ensure that the particle size is ≤45μm.

[0058] (2) Test and screen the components after grinding to ensure that the quality meets the requirements.

[0059] (3) The raw materials of the composite binder and the composite slow-release passivator are respectively fed into different mixers for thorough mixing.

[0060] (4) Add the mixed composite slow-release passivator raw material to the composite binder raw material and stir to mix, and add the solvent and stir at a speed of 300 rpm for 30 minutes to obtain the prebaked anode steel claw coating of this embodiment.

[0061] The prebaked anode steel claw coating of this embodiment is used to form a protective coating on the surface of the prebaked anode steel claw used in the aluminum electrolysis process. The specific method includes the following steps: (1) Pre-treatment of the surface of the anode steel claw by sandblasting to make it meet the rust removal grade Sa2.5. Sa2.5 rust removal grade standard: Thoroughly spray abrasives to completely remove rust and scale. After removing dust, the steel surface has a nearly white metallic luster with only tiny marks. (2) The pre-baked anode steel claw coating is applied to the surface of the pre-baked anode steel claw by spraying according to the standard method (the coating thickness is 120 μm).

[0062] (3) The steel claws coated with the paint are subjected to natural air drying and curing treatment. The natural air drying and curing time is 48 hours, and the anode steel claws coated with the protective coating are obtained.

[0063] The above-mentioned anode steel claws coated with protective coating were tested, and the test methods and results are as follows: The test method refers to the standard: GB / T 21776-2008 "Guide to the Testing Standards of Powder Coatings and Their Coatings". The adhesion, compressive strength and corrosion resistance of the coating were tested. The results are shown in Table 1.

[0064] Embodiment 4: The prebaked anode steel claw coating of this embodiment includes a composite binder, a composite slow-release passivating agent, a structural reinforcing agent, an auxiliary agent and a solvent (water).

[0065] The composite slow-release passivating agent includes the following components in parts by mass: 2 parts of sodium-based phosphate and aluminum-based phosphate (mass ratio is 1:1), 2.5 parts of chromate and nitrite (sodium chromate and sodium nitrite are selected in a mass ratio of 1:1 in this embodiment).

[0066] The composite binder includes the following components in parts by mass: 30 parts of aluminum sol, 15 parts of lithium water glass and 5 parts of calcium boride.

[0067] The structural reinforcing agent includes the following components in parts by mass: 25.5 parts of a framework material and 4.5 parts of kaolin, wherein the framework material includes barite, silica powder, mica powder and glass powder (the mass ratio is 1:1:1:1).

[0068] The auxiliary agent includes the following components in parts by weight: 0.5 parts of calcium borate, 0.3 parts of suspending agent, 1 part of dispersant and 1.5 parts of thickener.

[0069] The preparation method of the prebaked anode steel claw coating of this embodiment comprises the following steps: (1) Grind each component to ensure that the particle size is ≤45μm.

[0070] (2) Test and screen the components after grinding to ensure that the quality meets the requirements.

[0071] (3) The raw materials of the composite binder and the composite slow-release passivator are respectively fed into different mixers for thorough mixing.

[0072] (4) Add the mixed composite slow-release passivator raw material to the composite binder raw material and stir to mix, and add the solvent and stir at a speed of 300 rpm for 30 minutes to obtain the prebaked anode steel claw coating of this embodiment.

[0073] The prebaked anode steel claw coating of this embodiment is used to form a protective coating on the surface of the prebaked anode steel claw used in the aluminum electrolysis process. The specific method includes the following steps: (1) Pre-treatment of the surface of the anode steel claw by sandblasting to make it meet the rust removal grade Sa2.5. Sa2.5 rust removal grade standard: Thoroughly spray abrasives to completely remove rust and scale. After removing dust, the steel surface has a nearly white metallic luster with only tiny marks. (2) The pre-baked anode steel claw coating is applied to the surface of the pre-baked anode steel claw by spraying according to the standard method (the coating thickness is 120 μm).

[0074] (3) The steel claws coated with the paint are subjected to natural air drying and curing treatment. The natural air drying and curing time is 48 hours, and the anode steel claws coated with the protective coating are obtained.

[0075] The above-mentioned anode steel claws coated with protective coating were tested, and the test methods and results are as follows: The test method refers to the standard: GB / T 21776-2008 "Guide to the Testing Standards of Powder Coatings and Their Coatings". The adhesion, compressive strength and corrosion resistance of the coating were tested. The results are shown in Table 1.

[0076] Comparative Example 1: The prebaked anode steel claw coating of this comparative example comprises a binder, a composite slow-release passivating agent, an auxiliary agent and a solvent (water).

[0077] The composite slow-release passivating agent includes the following components in parts by mass: 2 parts of sodium-based phosphate and aluminum-based phosphate (mass ratio is 1:1), 1.5 parts of chromate and nitrite (sodium chromate and sodium nitrite in a mass ratio of 1:1 are selected in this comparative example).

[0078] The binder includes 47 parts by mass of aluminum sol.

[0079] The auxiliary agent includes the following components in parts by weight: 0.5 parts of calcium borate, 0.3 parts of suspending agent, 1 part of dispersant and 1.5 parts of thickener.

[0080] The preparation method of the prebaked anode steel claw coating of this comparative example is the same as that of Example 1.

[0081] The prebaked anode steel claw coating of this embodiment is used to form a protective coating on the surface of the prebaked anode steel claw used in the aluminum electrolysis process. The specific method includes the following steps: (1) Pre-treatment of the surface of the anode steel claw by sandblasting to make it meet the rust removal grade Sa2.5. Sa2.5 rust removal grade standard: Thoroughly spray abrasives to completely remove rust and scale. After removing dust, the steel surface has a nearly white metallic luster with only tiny marks. (2) The pre-baked anode steel claw coating is applied to the surface of the pre-baked anode steel claw by spraying according to the standard method (the coating thickness is 120 μm).

[0082] (3) The steel claws coated with the paint are subjected to natural air drying and curing treatment. The natural air drying and curing time is 48 hours, and the anode steel claws coated with the protective coating are obtained.

[0083] The above-mentioned anode steel claws coated with protective coating were tested, and the test methods and results are as follows: The test method refers to the standard: GB / T 21776-2008 "Guide to the Testing Standards of Powder Coatings and Their Coatings". The adhesion, compressive strength and corrosion resistance of the coating were tested. The results are shown in Table 1.

[0084] Comparative Example 2: The prebaked anode steel claw coating of this comparative example comprises a composite binder, a passivating agent, an auxiliary agent and a solvent (water).

[0085] The passivating agent includes: 3.5 parts by mass of sodium-based phosphate.

[0086] The composite binder includes the following components in parts by mass: 20 parts of aluminum sol, 15 parts of lithium water glass and 8 parts of calcium boride.

[0087] The auxiliary agent includes the following components in parts by weight: 0.5 parts of calcium borate, 0.3 parts of suspending agent, 1 part of dispersant and 1.5 parts of thickener.

[0088] The preparation method of the prebaked anode steel claw coating of this comparative example is the same as that of Example 1.

[0089] The prebaked anode steel claw coating of this embodiment is used to form a protective coating on the surface of the prebaked anode steel claw used in the aluminum electrolysis process. The specific method includes the following steps: (1) Pre-treatment of the surface of the anode steel claw by sandblasting to make it meet the rust removal grade Sa2.5. Sa2.5 rust removal grade standard: Thoroughly spray abrasives to completely remove rust and scale. After removing dust, the steel surface has a nearly white metallic luster with only tiny marks. (2) The pre-baked anode steel claw coating is applied to the surface of the pre-baked anode steel claw by spraying according to the standard method (the coating thickness is 120 μm).

[0090] (3) The steel claws coated with the paint are subjected to natural air drying and curing treatment. The natural air drying and curing time is 48 hours, and the anode steel claws coated with the protective coating are obtained.

[0091] The above-mentioned anode steel claws coated with protective coating were tested, and the test methods and results are as follows: The test method refers to the standard: GB / T 21776-2008 "Guide to the Testing Standards of Powder Coatings and Their Coatings". The adhesion, compressive strength and corrosion resistance of the coating were tested. The results are shown in Table 1.

[0092] Table 1 Coating performance test results of various embodiments and comparative examples

[0093] Table 2. Coating performance test results corresponding to different kaolin mass proportions in Example 2

[0094] The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments. For those skilled in the art, improvements and changes obtained without departing from the technical concept of the present invention should also be regarded as the protection scope of the present invention.

Claims

1. A prebaked anode steel claw coating, characterized in that: The composition comprises the following components in parts by weight: 5~50 parts of composite binder, 0.1~5 parts of composite slow-release passivator and solvent; The composite slow-release passivating agent comprises phosphate and corrosion inhibitor, wherein the phosphate comprises one or two of zirconium-based phosphate, aluminum-based phosphate, magnesium-based phosphate, calcium-based phosphate, chromium-based phosphate and sodium-based phosphate; the corrosion inhibitor comprises a combination of at least two of chromate, nitrate, nitrite, borate, tungstate, benzoic acid, zinc sulfate and acidic calcium carbonate; The composite binder comprises sol, water glass and a boron-containing compound.

2. The prebaked anode steel claw paint according to claim 1, characterized in that: The mass ratio of the phosphate to the corrosion inhibitor is 1:(1-2.5).

3. The prebaked anode steel claw paint according to claim 1, characterized in that: The sol includes at least one of aluminum sol and aluminum silicate sol; the water glass includes at least one of lithium water glass and potassium water glass; the boron-containing compound is one or two of boron oxide, boron nitride, titanium boride, borax, chromium boride, calcium boride and boric acid.

4. The prebaked anode steel claw paint according to claim 3, characterized in that: The mass ratio of water glass, boron-containing compound and sol in the adhesive is (5-50): (0.1-5): (5-20).

5. The prebaked anode steel claw paint according to claim 1, characterized in that: It also includes 5 to 30 parts by weight of a structural reinforcing agent, wherein the structural reinforcing agent includes a skeleton material and kaolin; the skeleton material includes at least one of barite, glass powder, silicon powder and mica powder; and the mass proportion of kaolin in the structural reinforcing agent is 5% to 50%.

6. The prebaked anode steel claw paint according to any one of claims 1 to 5, characterized in that: The invention also includes 0.1 to 6 parts by weight of an auxiliary agent, wherein the auxiliary agent includes at least one of calcium borate, a suspending agent, a dispersing agent and a thickening agent.

7. The prebaked anode steel claw paint according to any one of claims 1 to 5, characterized in that: The total ignition reduction rate of the prebaked anode steel claw coating is ≤10%, and the total organic component mass is ≤5%.

8. A method for preparing the prebaked anode steel claw coating according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) crushing the passivator, boron-containing compound and structural reinforcing agent of the prebaked anode steel claw coating separately or in combination, and controlling the particle size after crushing to be less than 150 μm; (2) The crushed raw material is mixed with other raw materials in proportion and a portion of solvent is added for wet grinding. After grinding, the particle size is controlled to be less than 45 μm, and the remaining solvent is added and mixed to obtain the prebaked anode steel claw coating.

9. The method for preparing the prebaked anode steel claw coating according to claim 8, characterized in that: In step (2), the stirring speed of the mixing operation is 200-500 rpm, and the mixing time is 15-60 min.

10. An application of the prebaked anode steel claw coating according to any one of claims 1 to 7 or the prebaked anode steel claw coating prepared by the preparation method according to any one of claims 7 to 8, characterized in that: The prebaked anode steel claw coating is used to form a protective coating on the surface of the prebaked anode steel claw used in the electrolytic aluminum process, and specifically includes the following steps: (1) The prebaked anode steel claw coating is uniformly applied on the surface of the prebaked anode steel claw by spraying or brushing; (2) Drying and curing the steel claw coated with the paint to obtain an anode steel claw coated with a protective coating.

Citation Information

Patent Citations

  • Long-life energy-saving anode conductive device for aluminum electrolysis

    CN115679388B

  • Steel claw for aluminum electrolysis and preparation method thereof

    CN116219324A

  • Method for coating aluminum and aluminum alloy anode steel claw

    CN117604436A

  • Anode using aluminum ash as raw materials, steel claw protection coating material and preparation method of coating

    CN107502014A

  • Coating for preventing oxidation of anode steel claw and preparation method thereof

    CN113072827A